Pengaruh Pola Komunikasi Remaja Surabaya terhadap Nasionalisme dalam Penggunaan Bahasa Indonesia - Diajeng Lailatul Sofya; Ela Mardianti; Farah Fariza; Devin Nabillah; Nabila Aulia; Eni Nurhayati (Pusat Riset dan Inovasi Nasional, 2024)
Communication and language are like important foundations to support various aspects of life. Language that is used effectively and according to a particular situation can give an expressive impression so that it can be well understood by the person you are talking to. As is the case with teenagers in Surabaya, even though they tend to use the typical Surabaya Javanese language known as boso suroboyoan, they still use Indonesian in certain situations. Therefore, our aim in conducting this research is to analyze patterns of influence on adolescent communication in Surabaya using qualitative methods which involve collecting and assessing journal sources and scientific papers as well as distributing questionnaires to search for adolescent respondents in Surabaya. This method is aimed at getting perspectives from Surabaya teenagers regarding the language that is often used in everyday communication.